Development of a New Data Processing System for Increasing the Accuracy of a Levitation Mass Method (LMM) based Measurement - Eko Satria; Hendro Hendro; Yusaku Fujii; Mitra Djamal (Newton-Maxwell Journal of Physics, 2021)
Levitation Mass Method (LMM) is the method as a material tester to evaluate the mechanical response of general objects against impact forces. In this method, a mass is made to collide with material to be tested and the impulse, i.e. the time integration of the impact force, is measured highly accurately as a change in momentum of the mass. To realize linear motion with sufficiently small friction acting on the mass, a pneumatic linear bearing is used. The inertial force acting on the mass is calculated from the velocity of the mass. The velocity is determined, highly accurately by means of measuring the Doppler shift frequency of a laser light beam reflected on the mass using an optical interferometer. To determine the Doppler frequency shift for LMM data processing, the method for estimating the frequency is necessary. Several methods have been developed to estimate the frequency for the LMM data processing with high accuracy, i.e. Zero-Crossing Average Method (ZAM), Zero-Crossing Fitting Method (ZFM), Sine Wave Fitting, and Zero-crossing Sine Wave Fitting. All methods realized using the zero-crossing point of the waveform obtained from the digitizer. A better method to estimate frequency on the digitized waveform will enable higher precision for a more accurate result. In this research, a new method that can improve the accuracy has been developed. The program was developed using data segmentation to obtain the frequency of the digitized waveforms. The developed program has the smallest error ( 1,98 X 10^-10 for N= 200) compare to other methods (2,31 X 10-3 for ZAM; 1,10X10-3 for ZFM; and 8,69 X10-4 for Zero-crossing Sine Wave Fitting).